Severe Corneal Edema in a Dog Naturally Infected by Leishmania spp. - Dower, Nathalie Moro Bassil; Amorim, Tássia Moara; Ribeiro, Alexandre Pinto; Dias, Álvaro Felipe de Lima Ruy; Sousa, Valéria Régia Franco (Acta Scientiae Veterinariae, 2020)
Background: Visceral leishmaniasis (VL) is an infectious disease caused by the protozoan Leishmania infantum that is transmitted to dogs and humans by sandflies. The incidence of eye injuries in VL is high. They occur in 20 to 81% of infected dogs and include blepharitis, granulomatous conjunctivitis, scleritis, keratitis, anterior uveitis, keratoconjunctivitis sicca, and secondary glaucoma. However, some dogs present only the clinical signs of eye damage. The main objective of this manuscript is to report a case of anterior uveitis with severe corneal edema in a dog with VL that underwent clinical and surgical ophthalmic treatments after miltefosine therapy. Case: An 8-month-old, intact male Labrador Retriever with brown fur presented with pruritus, diffuse desquamation, and conjunctival hyperemia on physical evaluation. On the basis of an ophthalmic examination, nodular conjunctivitis and uveitis were diagnosed in both eyes. Moreover, laboratory examination results showed hyperproteinemia, increased serum alkaline phosphatase activity, and positive reactions to immunochromatographic tests for VL. Clinical treatment was instituted from the moment of diagnosis, when miltefosine and allopurinol were prescribed. At the end of treatment, based on laboratory examination results, only allopurinol was prescribed at a lower dose than initially prescribed for treatment continuation. Topical medications (prednisolone eye drops and sodium hyaluronate) were recommended for the ophthalmic changes. One week after the start of topical treatment, the dog showed an improvement in eye inflammation but still had bilateral corneal edema. A hyperosmotic agent was prescribed to improve edema, and a surgical procedure was recommended if there was no improvement. The physician opted for the surgical procedure in one of the eyes that had not shown significant improvement after the clinical treatment. Discussion: VL is a zoonosis, and the domestic dog is the main reservoir. These animals often have dermatological conditions, and the ophthalmic changes observed can be unilateral or bilateral, with more than one change in the same eye. Lymphoplasmacytic or granulomatous anterior uveitis is the most prevalent change, as the uvea and conjunctiva are important lymphoid areas of the eye; this also explains the high incidence of uveitis and conjunctivitis in dogs with VL. In uveitis, corneal edema is driven by endothelial cell damage induced by prostaglandins, which interfere with the function of the endothelial pump and interrupt the normal dehydrated state of the cornea. Severe corneal edema can result in the formation of fluid-filled multifocal bubbles in the corneal stroma—a condition called bullous keratopathy. These bubbles accumulate under or inside the corneal epithelium, and they can burst spontaneously, leading to corneal erosions or ulcerations. Drug therapy with hyperosmotic agents could, in principle, reduce the formation of bubbles. Surgical options to decrease edema and blistering include a permanent conjunctival graft or thermokeratoplasty. Thermokeratoplasty induces the formation of superficial scars in the corneal stroma, applying multiple cauterization foci to the stroma exposed in the areas of bullous keratopathy and epithelial ulceration. In conclusion, the surgical therapeutic choice results in better visual quality in patients who do not respond well to clinical treatment.